Demographic Trends: Forecast of the Child Population from 0 to 3 years old for the Year 2030 - López Fuertes, Gandy René; López Fuertes, Gustavo Napoleón; Hernández Martínez, Jeimy Sugey; Naula Reina, Iván Cristian; Albuja Proaño, Guillermo Alexis (INGENIO, 2025)
This paper estimates the number of children aged 0-3 living in poverty in Ecuador, using combined data from the 2014 Living Conditions Survey (LCS) and the 2010 Population and Housing Census (CPV), as the current data do not provide sufficient detail by region. To do so, we employ the Small Area Estimation (SAE) method, based on the Fay-Herriot model, which uses multiple linear regression to integrate survey and census data. This approach allows the analysis of specific sub-populations, such as cantons or districts, where surveys alone do not provide reliable results due to small samples. In addition, consumption-based poverty is simulated and the child population is projected up to 2030, comparing these projections with estimates from the Economic Commission for Latin America and the Caribbean (ECLAC) to verify their accuracy. The main purpose of this research is to provide accurate and detailed information on children in poverty, thus supporting the creation of effective public policies in Ecuador.